FAKTOR YANG MEMENGARUHI ADOPSI TEKNOLOGI BIOPESTISIDA OLEH PETANI SAYUR DI SENDANA DAN PURANGI KOTA PALOPO - Piter Barto Tarukallo; Andi Alimuddin Unde (KAREBA : Jurnal Ilmu Komunikasi, 2014)
Abstract Biopesticide is one of the environmentally friendly technology that supports the development of organic farming, but biopesticides would be useless without the adoption. This research aimed (1) to investigate the decision to adopt the biopesticide technology by the vegetable horticulturalists in Sendana and Purangi Villages, Sendana Sub-District, Palopo City, (2) to investigate the effects of factors that affected the adoption of the biopesticide technology by the vegetable horticulturalists in Sendana and Purangi Villages. Sendana Sub-District, Palopo City. The research used descriptive approach with the quantitative research method. The data were collected using the sensus technique, i.e. involving the three horticulturalist groups who implemented the Integrated Pest Management program of the Farmer Field School (IPM FFS) in Organic Vegetables in Sendana and Purangi Villages, Sendana Sub-District, Palopo City. The data were then analyzed using Logistic Regression analysis Y = (P. Adoption / P. Was not adopted) C+β1X1+β2X2+ ...+ β19X19. The research revealed that the results of the Logistic Regression analysis variables X1 through X19 based on R Square Cox & Snell of 0.702 had positive effects on the variable Y. This indicated that 70.20% of the biopesticide adoption by the farmers as a group were influenced by the variable X, and the rest 18.40% influenced by other factors. The majority (71%) of the vegetable horticulturalists in Sendana and Purangi Villages, Sendana Sub-District, Palopo City had adopted the biopesticides technology in their farming activities.Abstrak Biopestisida merupakan salah satu teknologi ramah lingkungan yang mendukung pengembangan pertanian organik, namun biopestisida tidak akan berguna tanpa adanya adopsi. Penelitian ini bertujuan (1) mengetahui keputusan adopsi teknologi biopestisida oleh petani sayur di Kelurahan Sendana dan Purangi Kecamatan Sendana Kota Palopo, (2) mengetahui pengaruh antara faktor-faktor yang mempengaruhi adopsi dengan adopsi teknologi biopestisida oleh petani sayur di Kelurahan Sendana dan Purangi Kecamatan Sendana Kota Palopo. Penelitian ini menggunakan pendekatan deskriptif dengan metode penelitian kuantitatif. Metode penarikan atau pengambilan data dilakukan secara sensus yaitu melibatkan tiga kelompok tani yang melaksanakan program Sekolah Lapang Pengendalian Hama Terpadu (SL-PHT) Sayur Organik di Kelurahan Sendana dan Purangi Kecamatan Sendana kota Palopo. Data dianalisis dengan menggunakan analisis Regresi Logistik Y=(P. adopsi/P. tidak adopsi) C+β1X1+β2X2+ ...+ β19X19. Hasil penelitian menunjukkan bahwa hasil analisis Regresi Logistik menunjukkan bahwa variabel x1 sampai x19 berdasarkan R Square Cox & Snell sebesar 0,702 berpengaruh positif terhadap variabel y. Hal ini menunjukkan bahwa 70,20% adopsi biopestisida oleh petani secara bersama-sama dipengaruhi oleh variabel x dan sisanya 18,40% dipengaruhi oleh faktor lain. Petani sayur di Kelurahan Sendana Dan Purangi Kecamatan Sendana Kota Palopo sebagian besar (71%) telah mengadopsi teknologi biopestisida dalam kegiatan usaha taninya.